Prognosis of early breast cancer by immunohistochemistry defined intrinsic sub‐types in patients treated with adjuvant chemotherapy in the NEAT/BR9601 trial. Issue 6 (18th April 2013) - Ali, Alaa M.; Provenzano, Elena; Bartlett, John M.S.; Abraham, Jean; Driver, Kristy; Munro, Alison F.; Twelves, Christopher; Poole, Christopher J.; Hiller, Louise; Dunn, Janet A.; Earl, Helena M.; Caldas, Carlos; et al.
<x xml:space="preserve">Abstract</x> Breast cancer can be classified into molecular sub‐types that have distinct survival patterns. We evaluated the prognostic significance of breast cancer sub‐types in a cohort of women taking part in the NEAT and BR9601 clinical trials comparing cyclophosphamide, methotrexate and fluorouracil (CMF) with ECMF (epirubicin and CMF). Furthermore, we evaluated whether the sub‐types were predictive of the added benefit of epirubicin in these trials. Tumour tissue microarrays were stained and scored for ER, PR, HER2, EGFR and CK5/6. These were used to classify the tumours into six intrinsic sub‐types. We used Cox regression to compare overall survival (OS), breast cancer‐specific survival (BCSS) and relapse‐free survival (RFS) in the different sub‐groups. We also compared the effect of ECMF with CMF by sub‐group. Immunohistochemistry data were available for 1, 725 cases of whom 805 were luminal 1‐basal negative. Median follow‐up time was 7 years. The luminal 1‐basal negative tumours were associated with the best prognosis in five years after surgery and the HER2‐like tumours were associated with the poorest prognosis. There was little evidence for significant heterogeneity of this effect by tumour sub‐type (OS p = 0.40, BCSS p = 0.53 RFS p = 0.50) – the largest additional benefit of epirubicin was in women with tumours of the 5‐negative phenotype (OS HR = 0.39 95% CI: 0.21–0.73) and the smallest was in Luminal 1‐basal negative tumours (OS HR = 0.86 95% CI: 0.64–1.16). We confirmed that breast cancer sub‐types show distinct behaviour with differences in short‐ and long‐term survival. The benefit of ECMF over CMF was statistically similar in all disease sub‐types.